Analisis Peristiwa Era Orde Baru, Reformasi, dan Nilai Juang Mahasiswa dalam Novel Laut Bercerita - Febriyanti, Fauziah Dwi; Qotrunnada, Assifa Zanuba; Niswa, Lukluk Shafwatu; Syafira, Vira; Arochman, Taufik (Kajian Bahasa dan Sastra (KABASTRA), 2024)
The events of the new order and reformation in the novel The Sea Speaks His Name are one of the events that are interesting to explore further about reality that occurred at that time. The objectives of this research are 1) comparing the events in literary works with actual events, 2) identifying political issues in the new order and reformation, 3) analyzing the fighting value of the main character. The research method used is qualitative with a mimetic approach. The results of this research are that the events and issues in this novel are imitations of the reality of the new order and reformation era. In addition, the two main characters have fighting values that can be implemented in the real world.